The Security Factor in The Political Economy of Development - McGuire, Martin (IMF Working Papers; Working Paper ;, 1998)
A country's judiciary, police, and security forces are essential to protect the State from external aggression. By virtue of the State's monopoly of coercion, they maintain a stable legal framework and the safety of persons and property. All these activities enhance a society's productivity, but they also sustain the particular political regime-and its redistributive ethic-in power. They absorb resources, but they also waste them, since security forces tend to be rent-seekers. This paper analyzes both the productive and the unproductive side of security provision and shows that the balance depends on the nature of the political regime.